ROLE OF THE TEACHER IN ACTIVE LEARNING: EFL TEACHERS’ PERCEPTIONS, PRACTICES AND CHALLENGES OF IMPLEMENTATION - Tesfanesh Telore; Abebe Damtew (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
The current study was mainly aimed at exploring teachers’ perceptions, practices, and challenges of implementing their role in active learning. The total population of the study were 37 English language teachers in Kambata Tembaro Zone, Ethiopia. Data for the study were collected via a questionnaire and focus group discussion. The data collected via a questionnaire were analyzed quantitatively by using statistical package for social science and qualitative method of analysis was applied for the data gathered via focus group discussion. The findings of the study revealed that teachers lack clear understanding of their role in active learning and they were not properly accomplishing it in teaching the English language. Knowledge, skill, and aptitude gaps among teachers and students and unsuitable school environments were reported as major challenges affecting the implementation of active learning. Awareness creation and capacity-building workshops were recommended for the teacher and students to improve the implementation of active learning in secondary schools in Ethiopia.